PENGARUH KONSEP KAFA'AH DALAM MEMBINA KEUTUHAN RUMAH TANGGA - M. Amir Mahmud; Lukman Hakim; Abdul Hadijah (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
Marriage is an inner and outer bond between a man and a woman with the aim of forming a household that is sakinah mawadah and rahmah. To be able to realize this goal of course requires a harmonious and compatible partner. Islam offers kafa'ah as a medium so that the goals of marriage can be realized. Kafa'ah is equality or equality between a prospective husband and a prospective wife. In Islam, the most important equality that must be seen is in religious matters. Parents or married couples have different kafa'ah standards ranging from a social or religious perspective. For this reason, the research conducted by researchers aims to determine the application of kafa'ah in weddings in Gintangan village. This type of research is field research (field research) which is descriptive analysis in nature. The primary source in this research is the Gintangan village community using a proportional sampling technique, where the data sampling technique takes certain considerations into account, namely people who are married and parents who have married off their children. Data collection techniques use unstructured interview methods and documentation, qualitative data analysis techniques use inductive thinking methods, namely drawing conclusions starting from questions or specific facts leading to general conclusions.